DETERMINATION OF PASSING GRADE FOR EDUCATIONAL EQUALITY EXAM RESULTS IN PACKAGE C PROGRAM BASED ON PASSING COMPETENCY STANDAR - Oong Komar; Cucu Sukmana (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2022)
The background of this study is related to the complexity of canceling the 2020 UN implementation. However, it is said that graduates who graduate from the equivalent school unit/application through the easiest means have completed the study application during the COVID-19 pandemic as evidenced by means of playing card documents every semester, reaching the correct minimum attitude/behavior score and take the exam prepared through the school unit facilities. So that for now it no longer reaches the graduate competency standard (SKL). Meanwhile, the application of school equity (Package A, B, and C) is the flagship of non-formal schooling efforts to contribute to suppressing network problems that are hampered in gaining access to schools, drop outs and are constrained to enter the community. school offerings, especially competencies/lifestyle competencies, school offerings that remain complete and evolving through various packages on the network. Therefore, this discussion aims to provoke opportunities for answers to these problems through searching and finding product models for equality schools examining content material, especially based entirely on the competency requirements of graduates of package C applications at the school unit level. The concepts and theories used as references in this research consist of Community Education Concepts and Theories, school equity (Package A, B, and C), and academic tests mainly based on graduate competency requirements. This review uses the ADDIE type of study and development (R & D), this selection is mainly based entirely on the purpose of the study to provide a version of equivalence testing. The place of this research was carried out in PKBM bina Mandiri and Ash-shoddiq. The results of the experiment to create a product version of the equivalency school examination material are mainly based entirely on the competency requirements of the package C application graduates at the school unit level. For the future, this research can present a limitation in the assessment of equivalence education and provide an overview in the implementation of equivalence education.